Role of Venture Capital in Enterprise Innovation Under Psychological Capital and Heterogeneity of Entrepreneur Capital - Zhang, Chenjing; Mao, Di; Wang, Mancang (Frontiers in Psychology, 2020)
This paper is to explore the impact of entrepreneurial psychological capital and capital heterogeneity on venture capital behavior, and further analyze the effect of venture capital on the innovation activities of enterprises. Based on the existing research results, this paper proposes hypotheses on the relationship between venture capital and technological innovation. Based on the data samples of growth enterprises market (GEM) listed companies from 2010 to 2016, the main research variables are defined and a theoretical analysis model is constructed. The theory and empirical research clarify the relationship between venture capital and technological innovation. 1. According to the regression results of venture capital participation as well as innovation input and innovation output, the regression coefficients of venture capital participation are 0.609 and 0.203, which are significant at the levels of 10% and 1%, respectively. It indicates that venture capital participation has a positive impact on the innovation input and output of enterprises. 2. The coefficient of venture capital participation is positive, and the coefficient of is significantly negative. Therefore, the degree of product market competition has a significant moderating effect on the relationship between venture capital participation and technological innovation. Venture capital provides funding support for technological innovation in startups. At the same time, because it holds a certain percentage of shares, it participates in enterprise innovation activities and provides guidance for companies to maintain profitable growth, thereby improving their innovation awareness and level.